The Anatomy of Capitalist Society and Class Struggle in Emilia Perez (2024) on Marxist Perspective - Nur Safitri Hainaya; Putri Ayienda Dinanti (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This research analyzes the representation of the capitalist structure and the dynamics of class struggle within its system through a study of the film Emilia Perez (2024), utilizing the perspective of Marxism. The method employed is a descriptive qualitative approach based on Marxist critique. Data is collected from the characters dialogue, scenes, and visual representations, which showcase the conflict inherent in the capitalist environment. The analysis focuses on a critique of illicit activities within the capitalist setting and the struggle experienced by the social classes involved. The research verifies that the film strongly reflects that class contradiction within capitalism between the bourgeoisie and the proletariat. Furthermore, the film supports the Marxist analysis that the capitalist system maximizes absolute surplus value by employing economic power to modify legal frameworks. This demonstrates that the interest in capital accumulation becomes the primary objective, surpassing moral and legal boundaries.